DIREITOS HUMANOS E JUSTIÇA DE TRANSIÇÃO: Obstáculos para o cumprimento da sentença do caso Gomes Lund e outros Vs. Brasil - ROCHA, Felipe José Nunes (2017)
This dissertation analyzes, from a qualitative research based on the critical dialectical method, which are the obstacles that have prevented the Inter-American Court of Human Rights sentence rendered in Gomes Lund and others Vs. Brazil from being fully complished and the extent to which these obstacles compromise their potential contribution to the realization of transitional justice in the country and to the fight against human rights violations practiced by the Brazilian State. After the presentation of the human rights theory considered appropriate for the investigation and considerations of the configuration and functioning of the Inter-American Human Rights System, an analysis was made of the cases judged by the Inter-American Court that involved Brazil before the case Gomes Lund and others Vs. Brazil. Next, a critical analysis of the concept of transitional justice and the jurisprudence of the Inter-American Court on this matter was made. Then, after analyzing the Brazilian military dictatorship, the process of redemocratization of the country and the first justransicional measures adopted in Brazil, an approach was made on the “Guerrilha do Araguaia” and on the proceeding of the case Gomes Lund and others Vs. Brazil in the Commission and in the Inter- American Court of Human Rights. Finally, it was discussed about the judgment of the Inter- American Court rendered in the forementioned case, as well as to the measures taken by the Brazilian State to ccomplish it and the obstacles that have prevented its full accomplishment. The main conclusions reached are related to the fact that the prevalence of a normativeinstitutional approach in the Inter-American Court of Human Rights, as well as historical, cultural and political lements of the Brazilian scenario, has undermined the potential of the sentence to ontribute to the transitional justice in the country and to combat violations of human rights practiced by the Brazilian State.